Abnormal Communications of the Inferior Alveolar Nerve with Anterior Division of the Mandibular Nerve and the Lingual Nerve – A Case Report. - Prakashchandra S; Satheesha BN; Melanie RD (Department of Surgery, UKM Medical Centre, 2014)
Anomalous communications between the branches of posterior division of mandibular nerve are extensively reported due to their implication in various treatment procedures undertaken in the infratemporal region. We report an abnormal communication (CM1) between the anterior division of the mandibular nerve and the inferior alveolar nerve (IAN). The communicating branch was sufficiently thick and arose from the anterior division of mandibular nerve, traversed through the inferior head of lateral pterygoid muscle (LHLP) and united with the IAN on its lateral aspect, just at the mandibular foramen. Further there was a communication (CM2) between the IAN and the lingual nerve (LN). The communicating branch traversed downwards and forwards obliquely from the IAN before joining the LN. This communication was found deep to the LHLP. Knowledge of the current variation is important in two ways. Firstly, the CM1 might get compressed or pulled during the action of the LHLP as it passed through it; Secondly, Spix technique of IAN block might fail to give the desired effect as the CM1 joined IAN very close to the mandibular foramen.